2021
DOI: 10.1055/s-0041-1731602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat and Moisture Exchange Filter on the Dead Space Ventilation in a Pediatric Patient

Abstract: The use of heat and moisture exchange filter (HMEF) has become a routine standard of care in general anesthesia (GA), more so, during the current COVID-19 pandemic times. However its routine use, especially in pediatric patients, has several issues. We report a case of increased dead space ventilation in a pediatric patient due to the presence of HMEF. Hypercapnia and its cause was instantly diagnosed with two capnography sampling lines placed at two ends of the HMEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Of note, in small pediatric patients, it was reported that the dead space applied by HMEF induced CO 2 retention and EtCO 2 monitoring on the Y-piece side of HMEF failed to detect elevated CO 2 [ 10 , 27 ]. Our study results should not be applied to pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, in small pediatric patients, it was reported that the dead space applied by HMEF induced CO 2 retention and EtCO 2 monitoring on the Y-piece side of HMEF failed to detect elevated CO 2 [ 10 , 27 ]. Our study results should not be applied to pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that EtCO 2 measured with the sidestream method on the Y-piece side of HMEF showed lower values than that on the patient side [ 8 , 9 ]. Inaccurately low EtCO 2 values could lead to misrecognition of CO 2 retention and threaten patient safety [ 10 ].…”
Section: Introductionmentioning
confidence: 99%